Common polymorphisms of chemokine (C‐X3‐C motif) receptor 1 gene modify amyotrophic lateral sclerosis outcome: A population‐based study. Issue 2 (25th April 2017) - Calvo, Andrea; Moglia, Cristina; Canosa, Antonio; Cammarosano, Stefania; Ilardi, Antonio; Bertuzzo, Davide; Traynor, Bryan J.; Brunetti, Maura; Barberis, Marco; Mora, Gabriele; Casale, Federico; Chiò, Adriano
ABSTRACT: Introduction : In the brain, the chemokine (C‐X3‐C motif) receptor 1 ( 1CX3CR1 ) gene is expressed only by microglia, where it acts as a key mediator of the neuron–microglia interactions. We assessed whether the 2 common polymorphisms of the CX3CR1 gene (V249I and T280M) modify amyotrophic lateral sclerosis (ALS) phenotype. Methods : The study included 755 ALS patients diagnosed in Piemonte between 2007 and 2012 and 369 age‐matched and sex‐matched controls, all genotyped with the same chips. Results : Neither of the variants was associated with an increased risk of ALS. Patients with the V249I V/V genotype had a 6‐month‐shorter survival than those with I/I or V/I genotypes (dominant model, P = 0.018). The T280M genotype showed a significant difference among the 3 genotypes (additive model, P = 0.036). Cox multivariable analysis confirmed these findings. Discussion : We found that common variants of the CX3CR1 gene influence ALS survival. Our data provide further evidence for the role of neuroinflammation in ALS. Muscle Nerve 57 : 212–216, 2018